P02.06 Investigating the roles of IL-25 and ILC2s in APC-mutation-mediated colorectal cancer. (21st September 2022) - Jou, E; Hill, RJ; Murphy, JE; Rodriguez-Rodriguez, N; Ko, M; McKenzie, ANJ
Abstract : Background: Colorectal cancer (CRC) is the second leading cause of cancer-related death. The majority of CRC cases are caused by mutations in the adenomatous polyposis coli gene ( APC ), and are resistant to current cancer immunotherapies. Most immunotherapeutic strategies rely on utilising adaptive T cells, and their lack of efficacy in CRC suggests there may be immunosuppressive signals in the tumour microenvironment. Using a mouse model of APC -mutation-driven CRC, recent work by our lab has shown that interleukin 25 (IL-25)-activated group 2 innate lymphoid cells (ILC2s) promote intestinal tumourigenesis through activation of monocytic myeloid-derived suppressor cells (M-MDSCs) and the resulting suppression of CD8 + T cells. 1 However, the impact of IL-25 and ILC2s on individual intestinal tumour morphology is not completely understood. In this study, we use histological techniques to investigate the impact of genetic ablation of IL-25 or ILC2s on the morphology of APC-mutation-driven mouse intestinal tumours. Materials and Methods: The mouse strains used were Apc 1322T, Il25 tom, Il7ra Cre and Rora flox on a C57BL/6Ola genetic background. 1 Apc 1322T/+ Il25 tom/tom and Apc 1322T/+ Rora flox/flox Il7ra Cre/+ mice were used to investigate the effect of IL-25 deficiency or ILC2 deficiency, respectively, on intestinal tumours. Small intestinal tissue was fixed in 4% formaldehyde for 24 h and dehydrated. Intestines were embedded in paraffin and sectioned at 4 μm for histology, or 7.5% gelatin + 10% sucrose in PBS, followed by cryosectioning at 20 μm for immunohistochemistry. Paraffin sections were stained with hematoxylin and eosin (H&E) or Ki67 according to standard methods. For immunohistochemistry, cryosections were stained overnight at 4°C with fluorescent antibodies. Results: H&E images confirmed that transgenic Apc 1322T mice lacking IL-25 had smaller tumours and showed less dysplasia than Apc 1322T mice with normal IL-25 expression. Ki67 staining showed that tumours express higher Ki67 levels than adjacent normal intestinal tissue. The tumour-associated tertiary lymphoid structures (TATLS) of Apc 1322T mice lacking IL-25 appeared larger, indicating a more robust anti-tumour immune response. Likewise, Apc 1322T mice lacking ILC2s had smaller, less dysplastic tumours. TATLS in these mice were bigger than mice with ILC2s but smaller than Apc 1322T mice lacking IL-25, indicating that IL-25 may act via additional protumourigenic cell types. Immunohistochemistry confirmed the presence of ILC2s, as well as MDSCs the tumours of Apc 1322T mice, suggesting that these cells create an immunosuppressive niche. Conclusions: This pilot study confirms that genetic ablation of either IL-25 or ILC2s promotes anti-tumour immune reactions and decreases tumour size, correlating with reduced intestinal tumour proliferative capacity and dysplasia. Mice lacking IL-25 or ILC2s had larger TATLS, which are known to be associated with improved prognosis in patients. This study, along with previous data, highlights the potential therapeutic benefit of targeting the IL-25-ILC2 axis for colorectal cancer. Further studies are required to bring this from bench to bedside. Reference: Jou E, et al . An innate IL-25-ILC2-MDSC axis creates a cancer-permissive microenvironment for Apc mutation-driven intestinal tumorigenesis. Sci Immunol 2022 Jun 3;7 (72):eabn0175. Disclosure Information: E. Jou: None. R.J. Hill: None. J.E. Murphy: None. N. Rodriguez-Rodriguez: None. M. Ko: None. A.N.J. McKenzie: None.